To solve the quadratic equation \( 49x^2 = -392x - 784 \) using the perfect square trinomial pattern, let's first rearrange the equation:
-
Move all terms to one side of the equation:
\[ 49x^2 + 392x + 784 = 0 \]
-
Next, we can divide the entire equation by 49 to simplify it:
\[ x^2 + 8x + 16 = 0 \]
-
Now, notice that \( x^2 + 8x + 16 \) is a perfect square trinomial, as it can be factored as:
\[ (x + 4)^2 = 0 \]
-
Setting the factored equation equal to zero gives us:
\[ (x + 4)^2 = 0 \]
-
Taking the square root of both sides results in:
\[ x + 4 = 0 \]
-
Solving for \( x \):
\[ x = -4 \]
Thus, the solution to the quadratic equation is:
\[ \boxed{-4} \]
So, the correct response is \( x = -4 \).